Response to Pienemann's Critique of Zhang and Lantolf (2015). Issue 3 (23rd June 2015) - Lantolf, James P.; Zhang, Xian
<x xml:space="preserve">Abstract</x> We respond here to Pienemann's critique of our study that appeared earlier this year in the Language Learning Special Issue entitled "Orders and Sequences in the Acquisition of L2 Morphosyntax, 40 Years On" and guest edited by Jan Hulstijn, Rod Ellis, and Søren Eskildsen. Pienemann objected to our claim that the Teachability Hypothesis is a corollary of general Processability Theory; to our use of elicited imitation, one of the three tasks in our study, because only spontaneous speech can generate data that are relevant for assessing the predictions of Processability Theory and Teachability Hypothesis; and to our alleged departure from the requirements of Processability Theory with regard to what counts as evidence of a stage having been attained or not. We also address the issue of the relationship between morphological and syntactic development raised by Lenzing.